2017
DOI: 10.1093/mnras/stx017
|View full text |Cite
|
Sign up to set email alerts
|

Galaxies in the Illustris simulation as seen by the Sloan Digital Sky Survey - I: Bulge+disc decompositions, methods, and biases.

Abstract: We present an image-based method for comparing the structural properties of galaxies produced in hydrodynamical simulations to real galaxies in the Sloan Digital Sky Survey. The key feature of our work is the introduction of extensive observational realism, such as object crowding, noise and viewing angle, to the synthetic images of simulated galaxies, so that they can be fairly compared to real galaxy catalogs. We apply our methodology to the dust-free synthetic image catalog of galaxies from the Illustris si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 73 publications
0
34
0
Order By: Relevance
“…As such, the statistics of sky brightness, PSF resolution and crowding by nearby sources for real galaxies are reproduced in the synthetic images (along with any other field-dependent characteristics). The FullReal procedure is described in detail in Bottrell et al (2017a). We provide a summary here of the procedure that is followed for every synthetic image to compliment the public release of the realism suite 8 :…”
Section: Stellarmap Fullreal ( Smfr)mentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the statistics of sky brightness, PSF resolution and crowding by nearby sources for real galaxies are reproduced in the synthetic images (along with any other field-dependent characteristics). The FullReal procedure is described in detail in Bottrell et al (2017a). We provide a summary here of the procedure that is followed for every synthetic image to compliment the public release of the realism suite 8 :…”
Section: Stellarmap Fullreal ( Smfr)mentioning
confidence: 99%
“…Indeed, Huertas-Company et al (2019) used a similar but more rigorous approach with CNNs trained on the Nair & Abraham (2010) SDSS visual classification sample to perform Hubble type classifications of synthetic images of galaxies from the IllustrisTNG-100 simulations (Pillepich et al 2018;Nelson et al 2018;Rodriguez-Gomez et al 2019). Huertas-Company et al (2019) found that injecting the TNG images into real fields following the statistical observational realism approach of Bottrell et al (2017a) was crucial to obtaining consistent classification uncertainties when testing on SDSS and TNG images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can define a sample of early-type galaxies based on their more compact morphologies, more dispersion-dominated kinematics, redder colors and/or lower star-formation rates. The sole usage of a single individual criterion does not necessarily yield consistent galaxy-type determination (e.g., Bottrell et al 2017, Wang et al 2019, Donnari et al 2018. Therefore, we combine the light profile measured in the rest-frame SDSS r-band (Stoughton et al 2002) with the specific star-formation rate (sSFR) to classify typical central early-type galaxies for this study.…”
Section: Early-type Galaxy Classification and Sample Selectionmentioning
confidence: 99%
“…Briefly, Huertas-Company et al (2019)have selected galaxies with M st ar > 10 9.5 M in the snapshot 95 at z ∼ 0.045 and processed their images with the radiative transfer code SKIRT(Baes et al 2011, Camps & Baes 2015. The mock images are then observed in the SDSS r-band filter and further realism is added using RealSim 15(Bottrell et al 2017a,Bottrell et al 2017b, Bottrell et al 2019. The full procedure is outlined inRodriguez-Gomez et al (2019) andHuertas-Company et al (2019).…”
mentioning
confidence: 99%